Trens in food crop yields under demographic pressure in subSaharan Africa: the case of cassava in Southeast Nigeria - Enete, A.; Nweke, F.; Okorji, E. (SAGE Publications, 1995)
Research in 1973 attributed large cassava root yield differences among three villages in southeast Nigeria to equally large population density differences. In 1993, the Nigerian national team of the Collaborative Study of Cassava in Africa (COSCA) went back to the three villages to see whether population growth had led to yield declines. They found that the wide gap in yields between the high and low population density villages was maintained, apparently due to differences in soil type, fallow periods, cassava plant densities and harvest dates. Cassava root yield had doubled in the high population density area, increased but not doubled in the medium population density area and declined in the low population density area. The differences in the yield trends among the three villages were due to the use of improved cassava varieties in the high population density area.